Real-world Effectiveness of the Pfizer-BioNTech BNT162b2 and Oxford-AstraZeneca ChAdOx1-S Vaccines Against SARS-CoV-2 in Solid Organ and Islet Transplant Recipients. Issue 3 (4th January 2022) - Callaghan, Chris J.; Mumford, Lisa; Curtis, Rebecca M. K.; Williams, Sarah V.; Whitaker, Heather; Andrews, Nick; Lopez Bernal, Jamie; Ushiro-Lumb, Ines; Pettigrew, Gavin J.; Thorburn, Douglas; Forsythe, John L. R.; Ravanan, Rommel; et al.
Abstract : Background: The clinical effectiveness of vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in immunosuppressed solid organ and islet transplant (SOT) recipients is unclear. Methods: We linked 4 national registries to retrospectively identify laboratory-confirmed SARS-CoV-2 infections and deaths within 28 d in England between September 1, 2020, and August 31, 2021, comparing unvaccinated adult SOT recipients and those who had received 2 doses of ChAdOx1-S or BNT162b2 vaccine. Infection incidence rate ratios were adjusted for recipient demographics and calendar month using a negative binomial regression model, with 95% confidence intervals. Case fatality rate ratios were adjusted using a Cox proportional hazards model to generate hazard ratio (95% confidence interval). Results: On August 31, 2021, it was found that 3080 (7.1%) were unvaccinated, 1141 (2.6%) had 1 vaccine dose, and 39 260 (90.3%) had 2 vaccine doses. There were 4147 SARS-CoV-2 infections and 407 deaths (unadjusted case fatality rate 9.8%). The risk-adjusted infection incidence rate ratio was 1.29 (1.03-1.61), implying that vaccination was not associated with reduction in risk of testing positive for SARS-CoV-2 RNA. Overall, the hazard ratio for death within 28 d of SARS-CoV-2 infection was 0.80 (0.63-1.00), a 20% reduction in risk of death in vaccinated patients ( P = 0.05). Two doses of ChAdOx1-S were associated with a significantly reduced risk of death (hazard ratio, 0.69; 0.52-0.92), whereas vaccination with BNT162b2 was not (0.97; 0.71-1.31). Conclusions: Vaccination of SOT recipients confers some protection against SARS-CoV-2–related mortality, but this protection is inferior to that achieved in the general population. SOT recipients require additional protective measures, including further vaccine doses, antiviral drugs, and nonpharmaceutical interventions. Abstract :